2017
DOI: 10.22146/jieb.30298
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Disaggregation Strategy With Supplementary Displays Towards Balanced Scorecard Performance Evaluation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Yin also revealed that case studies study contemporary phenomena in real contexts and researchers have no control over those phenomena. In addition, case studies are a useful method in conducting evaluations (Kasingku, 2017). The research objects to be studied are 4 (four) perspectives used by BSC in formulating strategic planning at RSIY PDHI, namely financial perspective, customer perspective, internal business process perspective and growth and learning perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Yin also revealed that case studies study contemporary phenomena in real contexts and researchers have no control over those phenomena. In addition, case studies are a useful method in conducting evaluations (Kasingku, 2017). The research objects to be studied are 4 (four) perspectives used by BSC in formulating strategic planning at RSIY PDHI, namely financial perspective, customer perspective, internal business process perspective and growth and learning perspective.…”
Section: Methodsmentioning
confidence: 99%
“…Lipe and Salterio (2000) found that individuals tend to pay more attention to general measurements than unique measurements. On map E, it appears that in evaluation with BSC, general measurement bias is influenced by size type (Bone & Sholihin, 2012), disaggregation strategy (Kasingku & Goedono, 2017), and manager Involvement (Srirejeki, 2012).…”
Section: Article Classificationmentioning
confidence: 99%
“…(Bone & Sholihin, 2012) 6. (Kasingku & Goedono, 2017) 7. (Srirejeki, 2012) Map E analyzes management accounting practices for organizational control.…”
Section: Article Classificationmentioning
confidence: 99%